MULTILINGUAL COMMUNICATION IN K-POP: A TRANSLANGUAGING EXPLORATION OF WAYV'S YOUTUBE CONTENT - Alifa, Andina Rahma; Degaf, Agwin (Universitas Islam Sumatera Utara (UISU), 2024)
This study investigates the phenomenon of translanguaging among the multilingual members of the K-pop group WayV, focusing on their YouTube content,